Mechanical ventilation in patients with acute respiratory distress syndrome due to Covid-19 in an intensive care unit in Lima, Peru - Zegarra Piérola, Jaime (2022)
Objectives: To describe clinical, epidemiological, mechanical ventilation (MV) parameters and to determine overall mortality and that related to MV parameters in patients with acute respiratory distress syndrome (ARDS) in an ICU in Lima, Peru. Methods: A retrospective cohort including 133 patients with ARDS due to Covid-19 requiring MV in the Hospital Cayetano Heredia’s ICU was built from March to November 2020. Results: Males accounted for 75% of the cohort; 68% had no comorbidities; 97% has severe ARDS and 82% received extended 72h prone MV. Overall mortality was 38%; bivariate analysis found that alive patients had lower plateau pressure 27±1 cm H20 vs. 30±1 cm H20 (p=0.007), lower driving pressure 15±4 vs. 17±5 (p=0.008), higher static lung compliance 32±1 vs. 28±1 ml/cm H20 (p=0.01) and higher Pa02/Fi02 ratio 194±86 mm Hg vs. 157±66 mm Hg (p=0.01) than patients who died. Patients on extended prone MV had better survival (p=0.03). Conclusions: 97% of patients in the cohort had severe ARDS; overall mortality was 38%, alive patients had lower plateau pressure and less driving pressure and extended prone MV improved survival.